Transnational and International Dimensions of the Transitions - Sethelos Isidoros Balios; Antonio Muñoz Sánchez (Mélanges de la Casa de Velázquez)
The democratic transitions in Southern Europe in the 1970s were developed almost in parallel and attracted the enormous interest of international actors, such as the US and the EEC. Moreover, despite the peculiarities and the different origins of each case, the transitions resulted in the establishment of democratic systems, fully integrated in the EEC. This article aims to focus both on the international dimensions of the transitions, as well as on the possible transnational interactions of the democratization in Spain, Portugal and Greece. In addition, it addresses these issues through three chapters. In the first, the article examines the international relations of the Iberian regimes and Greece with the most important international actors, most notably the US and the EEC, the second chapter focuses on the influence these actors had during the transitions and the third chapter on the implications the EEC integration process had on the relation between the three countries.